Spectrophotometric determination of phosphate in matrices from sequential leaching of sediments. (18th January 2016) - Anschutz, Pierre; Deborde, Jonathan
Abstract: The speciation of Phosphorus (P) in geologic materials can inform diverse investigations in such as aquatic biogeochemistry, soil sciences, and paleo‐oceanography. Here, we describe in detail a set of sequential extraction schemes to measure P concentrations from several operationally defined phases: pore water, exchangeable or loosely sorbed P, Fe‐bound P, P associated with biogenic apatite, P associated with authigenic apatite and carbonate forms, P associated with detrital apatite and inorganic forms, and organic P. The two benefits of the procedures we describe compared to prior methodological studies are: (1) fast, simple and inexpensive colorimetric methods have been developed for P determination in all the different matrices; and (2) the Fe‐bound phosphorus pool is separated into two fractions, allowing the P associated with most reactive Fe‐fraction to be distinguished from P bound to the remainder of the Fe‐oxides. Adaptations of these procedures to optimize the characterization of P pools in a range of material types are also outlined.